G2. Low pregestational fat mass and subsequent maternal cardiovascular maladaptation in early pregnancy. The missing link for preeclampsia. (12th August 2016) - Presti, D. Lo; Gagliardi, G.; Tiralongo, G. M.; Pisani, I.; Farsetti, D.; Scala, R. L.; Novelli, G. P.; Vasapollo, B.; Andreoli, A.; Valensise, H.
Abstract: Introduction : Several studies have demonstrated the correlation between maternal obesity and pregnancy complications. Obese women seem to be at higher risk to develop late preeclampsia, which shows a more favorable perinatal outcome compared to the early form. The assessment of total vascular resistance (TVR) could play an additional role in the detection of these patients. Targets : To identify patients at higher risk of hypertensive complications through the assessment of pre-pregnancy maternal fat mass (FM) and TVR. Results : Patients were divided into two groups in the first trimester: group A with low TVR and group B with high TVR. Cardiac output, stroke volume and TVR were statistically different at preconceptional visit and during the first trimester. FM was the only bioimpedance parameter to be found significantly different, higher in group A (Table 1 ). In group A, it is possible to identify a subgroup with higher FM that could be at high risk of late preeclampsia difficultly recognizable throughout TVR and BMI (Figure 1 ). On the other side, a too low FM might negatively influence maternal adaptation to pregnancy. Conclusions : FM could represent a better marker of body composition and a target to monitor the effectiveness of dietary changes improving maternal and neonatal outcome.